Uma luz na voz do invisível: a experiência de ser mãe para usuário de crack - Bastos, Maria do Socorro Furtado (2014)
This research had as main objective to understand the experience of motherhood in crack smokers. Specific description of how was the experience of these women know / feel pregnant and understanding how it presented the child care and self-care goals. The subjects were mothers of women crack users. The methodology was qualitative grounded in existential phenomenology. Thus, we collected narratives of research subjects, as well as the narrative of the researcher, is facing its affect on the meeting with these women, through their action. Five women were interviewed. The theoretical framework authors took as Heidegger, Foucault and Benjamin. The analysis considered the philosophical hermeneutics of Gadamer. As a result presented the unveiling of the unique universe of women in their experiences with motherhood. Could not grasp the phenomenon of mother feel in their narratives. As the phenomenon of abandonment, rejection, stigma, violence and the relationship established with the substance where possible to reflect on the ontic way of living today.